Optimal local content for extractive industries: How can policies best create benefits for Tanzania? - Mia Ellis; Margaret Stokes McMillan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Tanzania is rich with natural resources, which have significant potential to contribute to the country's economic development. Several laws recently passed in Tanzania are dedicated to establishing linkages between foreign firms in natural resource extraction and the local economy. This paper documents this legislation and the institutions set up to enforce and monitor these laws. Effectiveness of local content legislation and the potential for firms in the mining sector to contribute to local development are then evaluated using a combination of qualitative and quantitative evidence. We then examine other developing countries' experiences with local content legislation, drawing lessons for Tanzania.
Keywords: O13; N5; Q38; L71; L72; 330; extractive industries; local content; mining; natural gas; natural resources